The agency of students, teachers and learning technologists - Frances Bell (Association for Learning Technology, 2009)
The articles in this issue reveal the commitment of ALT-J to publish research that addresses the perspectives of a range of stakeholders in learning technology: in this case, students, teachers and learning technologists themselves. Although the articles are wide-ranging in their scope and approaches, we can detect some important and common themes. The first of these is agency: learning technology research can fall into the trap of focusing on the technology that is offered rather than what people do with or without it. The second is online discussion: although computer conferencing has been used in education since the 1980s, student engagement remains a thorny issue for practice, and one that demands additional research. Thirdly, the role of learning technologists remains in question: how can they support staff and students through their practice and research?